Levels of interest among prospective and enrolled undergraduate students in learning through online and blended modes - Brown, B.; Mbewe, A.; Forcheh, N. (South African Journal of Higher Education, 2023)
In many developing countries, at least in Africa, many colleges and universities continue to deliver undergraduate level education in the in-person, face-to-face, mode. Many of these institutions are slow in adopting and embracing the online learning mode. This study investigated levels of interest among prospective and enrolled undergraduates for the full-online or blended learning mode. The study also assessed the factors that stimulated the interest of these groups for the preferred delivery mode. Based on a sample of 414 prospective and enrolled undergraduates from private and public colleges and universities in the context of Botswana, and using a survey design that involved questionnaires, and regression analysis, the study found that majority (56%, n=414) of the sample was interested in and preferred some form of online or blended learning, compared to the face-to-face learning mode. The proportion of individuals with keen interest in the blended learning mode, at undergraduate level, is surprisingly high. The motivational drivers for the student choice are linked to greater flexibility and convenience, and perceived better opportunity for interactions with professors and classmates (OR=10.9; 95% CI: 5.4 – 22.1). The COVID-19 outbreak and the requirements for social distancing may have also accounted for the level of interest reported. The findings have major significance for curriculum design and development, instructional design in higher education, education technology infrastructure development, and long-term enrolment planning.